Is the elimination of ‘sleeping sickness’ affordable? Who will pay the price? Assessing the financial burden for the elimination of human African trypanosomiasis Trypanosoma brucei gambiense in sub-Saharan Africa - C Simone Sutherland; Fabrizio Tediosi (BMJ Global Health)
Introduction Programme to eliminate neglected tropical diseases (NTDs) have gained global recognition, and may allow for improvements to universal health coverage and poverty alleviation. It is hoped that elimination of human African trypanosomiasis (HAT) Trypanosoma brucei gambiense (Tbg) would assist in this goal, but the financial costs are still unknown. The objective of this analysis was to forecast the financial burden of direct costs of HAT Tbg to funders and society.Methods In order to estimate the total costs to health services and individuals: (1) potential elimination programmes were defined; (2) the direct costs of programmes were calculated; (3) the per case out-of-pocket payments (OOPs) by programme and financial risk protection indicators were estimated. The total estimated costs for control and elimination programme were reported up till 2020 in international dollars. The mean results for both direct programme costs and OOPs were calculated and reported along with 95% CIs.Results Across sub-Saharan Africa, HAT Tbg maintaining ‘Control’ would lead to a decline in cases and cost US$630.6 million. In comparison, the cost of ‘Elimination’ programme ranged from US$410.9 million to US$1.2 billion. Maintaining ‘Control’ would continue to cause impoverishment and financial hardship to households; while all ‘Elimination’ programme would lead to significant reductions in poverty.Conclusion Overall, the total costs of either control or elimination programme would be near US$1 billion in the next decade. However, only elimination programme will reduce the number of cases and improve financial risk protection for households who are impacted by HAT Tbg.